2020
DOI: 10.1039/c9an02309g
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive “ON–OFF” fluorescent probe based on carbon dots for Fe2+ detection and cell imaging

Abstract: A sensitive fluorescent probe based on carbon dots has been synthesized by a one-pot hydrothermal method for the rapid detection of intracellular Fe2+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…High‐resolution spectra (inset in Figure 1a) showed that the core of CA‐CDs possessed a crystal diffraction stripe and network lattice, which are similar to those of a graphite structure. [ 25 ] As shown in Figure 1b, the main size distribution of CA‐CDs was between 3.8–10.1 nm, and Gaussian fitting provided an average size of approximately 6.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…High‐resolution spectra (inset in Figure 1a) showed that the core of CA‐CDs possessed a crystal diffraction stripe and network lattice, which are similar to those of a graphite structure. [ 25 ] As shown in Figure 1b, the main size distribution of CA‐CDs was between 3.8–10.1 nm, and Gaussian fitting provided an average size of approximately 6.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, it is difficult to establish a highly specific probe for the detection of Fe 2+ , because the different oxidation states of Fe 2+ and Fe 3+ vary with each other. On the other hand, due to the strong force between paramagnetic Fe 2+ and fluorophore, fluorescence quenching is usually induced, resulting in part of the constructed probes being “on-off” type, which is not easy to observe due to the influence of spontaneous fluorescence of organisms ( Wei et al, 2020 ). Currently, the Fe 2+ fluorescent probes mainly include N-oxides, nitroxyl radicals, endoperoxides, bionic ligands, heavy metals, imines and so on.…”
Section: Probes For Ironmentioning
confidence: 99%
“…The results show that the addition of Fe 2+ with the probe solution improved the magnetic intensity of fluorescence by 6-fold. Wei et al ( Wei et al, 2020 ) developed a “on-off” fluorescent probe based on a carbon point (CDs), which has been efficiently used to detect Fe 2+ in BSA solution, tap water and living cells ( Figure 4A ). In order to realize real-time detection of unstable ferric divalent ions in living systems, Long et al ( Long et al, 2018 ) designed a fluorescent probe of coumarin by using a unique cyclization reaction.…”
Section: Probes For Ironmentioning
confidence: 99%
“…To our knowledge, although fluorescent CDs have been widely utilized in the detection of intracellular iron ions based on the fluorescence quenching effects of iron ions [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], most of them were developed for the monitoring of trivalent ferric Fe 3+ ions [ 10 , 11 , 12 , 13 , 14 , 15 ]. Few reported CDs have been designed for specific detection of divalent ferrous Fe 2+ ions over ferric ions [ 18 , 19 , 20 ] and successfully applied to monitor the intracellular Fe 2+ ions [ 16 , 21 ]. Ferrous ions enhance oxidative stress by catalyzing the production of reactive oxygen species that induce biochemical signaling processes, leading to degenerative diseases such as cancer, Alzheimer’s disease, and Parkinson’s disease [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%